2019
DOI: 10.1080/09712119.2019.1599900
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nine growth curve models to describe growth of partridges(Alectoris chukar)

Abstract: In this study, nine non linear growth curve models were used to determine the goodness of fit by the body weight measurements of the total number of 178 partridges(Alectoris chukar), 93 females, and 85 males, respectively. The R 2 (coefficients of determination) values for the total partridges, females and males in Brody,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 13 publications
(26 reference statements)
3
17
0
Order By: Relevance
“…Body weight is one of the most significant traits in poultry production because it is associated with growth rate, feed conversion efficiency and occurrence of diseases in a flock (Amraei et al 2017). Poultry growth patterns have been predicted using different mathematical models (Darmani et al 2003;Sengul and Kiraz 2005;Roush and Branton 2006;Yaya et al 2019). Several factors both nongenetic (health, age, welfare, location and feed) and genetic (breed or strain) have been implicated in the huge variations in growth curves fitted to the mathematical models (Darmani et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Body weight is one of the most significant traits in poultry production because it is associated with growth rate, feed conversion efficiency and occurrence of diseases in a flock (Amraei et al 2017). Poultry growth patterns have been predicted using different mathematical models (Darmani et al 2003;Sengul and Kiraz 2005;Roush and Branton 2006;Yaya et al 2019). Several factors both nongenetic (health, age, welfare, location and feed) and genetic (breed or strain) have been implicated in the huge variations in growth curves fitted to the mathematical models (Darmani et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Riazoshams et al (2019) discussed different robust non-linear regression models, and Satoh (2019) worked on the model selection procedures for various growth models having an equal number of parameters. Wen et al (2019) compared nine different growth models for describing the growth of partridges. Dharmaraja et al (2020) investigated an empirical analysis for crop yield production forecasting in India, while Lavanya et al (2020) explored a multiple linear regressions model for crop production prediction using the Adam optimizer and the Neural Network Mlraonn.…”
Section: Introductionmentioning
confidence: 99%
“…,Kaplan and Gurcan (2018),Nimase et al (2018),Riazoshams et al (2019),Satoh (2019),Wen et al (2019),Murugan et al (2020) andGuo et al (2021) worked on different growth models and showed the best model through the measures of model adequacy for different crops and for different areas of applications. Different growth models suggested by above authors are given below.…”
mentioning
confidence: 99%
“…The growth curve parameters determination, effectively, describe issues such as growth, livestock performance and optimum slaughter age, as well as preparing an appropriate feeding process and selection (Sariyel et al, 2017). As for partridges, these parameters facilitate the judgment and analysis the standards of feeding, management and epidemic prevention, and to compare and test the genetic quality of different genders (Wen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%